Tindak Tutur Ilokusi Direktif dan Ekspresif dalam Film Preman Bange Episode 1-29 di Youtube Pagaralam Channel - Indriyani, Bertha; Nopriani, Henny; Tansilo, Hikma (Bastrando: Jurnal Bahasa dan Sastra Indonesia, 2024)
The formulation of the problem in this study is How is the directive and expressive illocutionary speech acts in the film Preman Bange episode 1-29 on youtube Pagaralam channel? The purpose of this study is to describe the directive and expressive illocutionary speech acts in the film Preman Bange episode 1-29 on youtube Pagaralam channel. This research method uses descriptive method, based on the results of the study obtained four directive speech acts namely commanding, requesting and advising speech acts, and recommending sema with directive speech acts, while expressive speech acts found three speech acts namely saying thank you, apologizing and criticizing. From the movie Preman Bange episode 1-29, 110 directive and expressive speech acts were obtained, including 77 directive speech acts and 33 expressive speech acts, the directive speech act of commanding obtained 72 utterances, the directive speech act of asking obtained 3 utterances, and the speech act of advising obtained 7 utterances, while the expressive speech act of thanking obtained 15 utterances, the speech act of apologizing there were 8 utterances, and the expressive speech act of criticizing obtained 3 utterances.